The mass litigation in the social jurisdiction - Gómez Abelleira, Francisco Javier (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
Mass litigation in the labour jurisdiction adopts different procedural techniques, such as collective actions and joinder of parties. The procedural reform of 2023 (RDL 6/2023) has introduced two new techniques into the jurisdiction: the test claim and the extension of the effects of a final judgment to third parties. This article analyzes these new developments regarding mass litigation, studying their relationships with traditional collective proceedings.
Keywords: Mass litigation; collective action; test claim; extension of final judgment to third parties; joinder of parties